#TITLE_ALTERNATIVE# - Herawan (NIM 123 03 022), Fitriyanda
Abstract : Multiattribute analysis process is made in Formation X field FY which located at central sumatera basin in PT. Chevron Pacific Indonesia operation area. Seven wells are used in this study. These wells are chosen because they have complete well data and have a good correlation with seismic at well-seismic tie process. The best wavelet that is used is bandpass wavelet with low cut 5 Hz, low pass 20 Hz, high pass 40 Hz, dan high cut 80 Hz. In inversion process, horizon top X is used. Initial model is made with control of those seven wells and one horizon. Three inversion type are applied to the initial model which are a) Bandlimited inversion b) Modelbased Constrained inversion and c) Sparse-spike Maximum Likelihood inversion. The best inversion technique is Modelbased Constrained inversion. Relative impedance volume was made from the subtractions of modelbased volume with initial model volume. Those two volumes are then used for become external attributes for the making of pseudo-log volume from multiattribute analysis process. Pseudo-gamma ray volume, pseudo p wave volume (which only became external attribute) and pseudo-porosity volume are made. Pseudo-gamma ray volume and pseudo-porosity volume are used to make isochron map, porosity thickness map, average gamma ray map, average porosity map, and net to gross ratio map. Those maps gave a good consistency and were then interpreted for next field development.